(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
The decline in estrogen hormone levels among elderly women who have entered the menopausal phase contributes to a deterioration in their overall health condition. One of the prominent effects is a reduction in muscle performance, which in turn leads to decreased muscle strength and diminished balance control. This community service program was designed with the following objectives: (1) to enhance elderly women’s understanding of the symptoms of knee osteoarthritis, its prevention strategies, management approaches, and the associated risk of falls; (2) to conduct preventive health efforts through early detection of knee osteoarthritis using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) questionnaire and goniometer, and early detection of fall risk using the Timed Up and Go (TUG) test; and (3) to provide a lower-limb muscle strengthening exercise program. The activity was attended by 52 elderly women aged over 60 years residing in Gulingan Village in July 2025. The results of the knowledge regarding knee osteoarthritis and fall risk increased from 32,7% to 82,7%. Early detection using the WOMAC questionnaire revealed that the majority of participants were at a mild risk of knee osteoarthritis (80.78%). Goniometer measurements indicated that most participants maintained a normal range of joint motion. Furthermore, early detection using the TUG test demonstrated that the majority of elderly women had a low risk of falls (80.8%). This program successfully increased awareness and preventive behavior among elderly women, highlighting the importance of early screening and home-based strengthening exercise.